Documenting a labor of love: emotional labor as academic labor. Issue 2 (3rd April 2018) - Lawless, Brandi
ABSTRACT: Neoliberal practices embedded in academia have transformed the university into a service industry. Through this lens, this review documents the current exploration of emotional labor in academia, specifically in communication studies. While a paucity of literature on this topic exists, I explore how a neoliberal agenda creates an expectation for communication faculty to perform emotional labor (and how this expectation is greater compared with other fields), the ways in which emotional labor is differentially experienced for women, and how communication studies as a gendered field exacerbates expectations to perform such labor. Moreover, I highlight the shifting perception of the field and the related moves to expand emotional labor. Finally, I discuss ways to move forward in a neoliberal academia.